The role of AGT, AMPD1, HIF1a, IL-6 gene polymorphisms in the athletes` power status: a meta-analysis - Ipekoglu, G.; Cetin, T.; Calcali, T.; Apaydin, N.; Senel, E. (Journal of Human Kinetics, 2023)
This meta-analysis was designed to investigate the relationship between genetic polymorphisms (AGT rs699, AMPD1 rs17602729, HIF1a rs11549465, IL-6 rs1800795) and power athletes` status. Only case-control studies were included in the meta-analysis. A systematic search of the PubMed and Web of Science databases was performed to identify relevant studies and 23 studies met the inclusion criteria for the meta-analysis. The data from the included studies were pooled and analyzed using a random effects or fix effects model. The effect size was calculated as the odds ratio or a risk ratio with 95% confidence intervals. The results showed that certain genetic polymorphisms, AGT rs699 Thr allele, HIF1A rs11549465 Ser allele and AMPD1 rs17602729 C allele, were significantly more prevalent in power athletes (p < 0.05). When examining the genotype frequency distribution of AGT rs699 and AMPD1 rs17602729, significant differences were found in both the dominant and recessive models (p < 0.05). The results indicate that these gene polymorphisms play a role in power athlete status, however, new and more comprehensive studies are needed to confirm these results.